Degradation of Phenolic Compounds Using Pseudomonas aeruginosa and Enterobacter cloacae Bacteria in Groundwater (Case Study: Gempolsari Village) - Aulia Nur Febrianti; Dwi Ramadya Risqiana Putri; Rhenny Ratnawati (Journal of Science and Engineering, 2026)
The Lapindo mudflow disaster in Porong, Sidoarjo, has caused long-term environmental contamination, particularly affecting groundwater quality in surrounding residential areas such as Gempolsari Village. One of the major pollutants identified in contaminated groundwater is phenol, an aromatic hydrocarbon compound that poses significant risks to both human health and aquatic ecosystems. This study aimed to evaluate the effectiveness of Pseudomonas aeruginosa and Enterobacter cloacae in degrading phenol compounds in groundwater contaminated by Lapindo mudflow under aerobic conditions. The biodegradation experiment was conducted using three treatment variations, namely variation A (Pseudomonas aeruginosa : Enterobacter cloacae = 10:0), variation B (5:5), and variation C (0:10). Prior to treatment, groundwater quality parameters including pH, temperature, dissolved oxygen, and phenol concentration were analyzed. Observations of bacterial growth, pH changes, and phenol degradation were carried out at 6, 12, and 18 hours. The results showed that all treatment variations were capable of degrading phenol effectively, achieving complete phenol removal at the 18th hour. However, variation C demonstrated the best performance during the intermediate observation period, reducing phenol concentration from 0.0089 ppm to 0.0046 ppm at the 12th hour with a degradation efficiency of approximately 72.6%. The pH values remained stable within the range of 6–7, indicating favorable environmental conditions for bacterial activity. In addition, bacterial population growth observed throughout the experiment confirmed the ability of both bacterial species to adapt and utilize phenol as a carbon and energy source. These findings indicate that Pseudomonas aeruginosa and Enterobacter cloacae have strong potential for application in the bioremediation of phenol-contaminated groundwater affected by Lapindo mudflow.